Cross-Cultural Design. Cultural Differences in Everyday Life 5th International Conference, CCD 2013, Held as Part of HCI International 2013, Las Vegas, NV, USA, July 21-26, 2013, Proceedings, Part II - Rau, P.L.Patrick.; Rau, P.L.Patrick. (Information Systems and Applications, incl. Internet/Web, and HCI ;, 2013)
This is the second part of the two-volume set (LNCS 8023-8024) that constitutes the refereed proceedings of the 5th International Conference on Cross-Cultural Design, held as part of the 15th International Conference on Human-Computer Interaction, HCII 2013, held in Las Vegas, USA in July 2013, jointly with 12 other thematically similar conferences. The total of 1666 papers and 303 posters presented at the HCII 2013 conferences was carefully reviewed and selected from 5210 submissions. These papers address the latest research and development efforts and highlight the human aspects of design and use of computing systems. The papers accepted for presentation thoroughly cover the entire field of human-computer interaction, addressing major advances in knowledge and effective use of computers in a variety of application areas. This two-volume set contains 113 papers. The papers in this volume focus on the following topics: cultural issues in business and industry; culture, health and quality of life; cross-cultural and intercultural collaboration; culture and the smart city; cultural differences on the Web.